Management of Thusta viranam (Chronic diabetes mellitus associated venous leg ulcer) by using Traditional treatment regimen: A case study: Shomesh V.1, Yameni K.2, Keerthika C. 2, Kasthuri S. 2, Soruban T.3 and Subaveena S. 2 (Sri Lanka Journal of Indigenous Medicine (SLJIM), 2025)
Chronic wounds, such as venous leg ulcers, are common and often persist for weeks or months. One type, Thusta viranam, described in Traditional and Siddha literature, is characterized by deep, purulent, foul-smelling wounds with severe pain, swelling, and itching. Traditional and Siddha medicine recommends various topical and oral treatments to promote healing. Punsudar thailam, mentioned in Anuboga Vaithiya Navaneedha Thirattu, is used for wound healing and contains purified Sulphur (Ganthagam) and castor oil. This case study investigates the efficacy of Punsudar thailam in treating a Thusta viranam (Chronic diabetes mellitus associated venous leg ulcer). A 52-year-old female with a three months history of a painful, swollen, foul-smelling wound due to varicose veins, located above the lateral malleolus of her left leg, was admitted to the Siddha Teaching Hospital in Kaithady. The patient also had a history of diabetes, hypertension, dyslipidaemia, and fatty liver disease. She was diagnosed as Thusta viranam (chronic diabetes mellitus associated venous leg ulcer) and treated with wound cleaning using Panjathuvarpi decoction (Kudineer), followed by Punsudar thailam application and oral internal medicines such as Neermulli decoction (Kudineer), Pattolathy peerkku decoction (Kudineer), Sudarsana chooranam, Chandraprabha vati, and Vallarai chooranam. The treatment was evaluated weekly through wound measurements and photographs using the Photographic Wound Assessment Tool (PWAT). Over a period of 29 days, weekly evaluations showed a reduction in wound size from 5cm x 5cm to 3cm x 3.5cm with near complete closure (<0.1 cm). The PWAT score decreased from 17 to 07, indicating partial wound closure. These results suggest that Punsudar thailam, combined with internal medicines, effectively aids in healing Thusta viranam (chronic diabetes mellitus associated venous leg ulcer).